Comparation of the Concept of Insan Kamil Ibn 'Arabi and Abraham Maslow's Self Actualization - M. Rifqi Aminul M; Achmad Khudori Soleh (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
This research aims to comparatively analyze the philosophical spiritual dimension of Ibn ‘Arabi’s concept of insan kamil and the humanistic–psychological dimension of Abraham Maslow’s theory of self-actualization, particularly in relation to their views on the meaning of life and human perfection. This study is significant as it explores how these two frameworks rooted in Islamic metaphysics and modern humanistic psychology offer distinct yet potentially complementary perspectives for addressing the challenges of achieving existential balance and authentic self-actualization in the modern era. This research aims to identify the similarities and differences between the concepts of insan kamil and self-actualization and how they are applied in life. The research method uses qualitative with a literature study approach which involves content analysis from several literature sources. Results of this research; 1) perfect human being tajalli God and fully practice the teachings of the Prophet Muhammad. 2) Self-actualization as a peak experience provides psychological and physiological mystical experiences as well as an expanded outlook on life. 3) The combination of human beings with self-actualization provides a deep understanding of oneself, spiritual experience, social responsibility, and understanding of human dignity. 4) This research contributes to academic literature and can be a guide for psychological and spiritual self-development.